Classical electrodynamics - Jackson, John David (New Delhi: John Wiley & Sons, 1999)
This book covers information relating to physics and classical mathematics that is necessary to understand electromagnetic fields in materials and at surfaces and interfaces. It also addresses the changes in emphasis and applications that have occurred in the past twenty years.
Includes bibliographical references.; Appendix 775-784p.; Bibliography 785-790p.; Index 791-808p.
Keywords: Electrodynamics; Physics